ANTARA INOVASI DAN KOLABORASI: PERAN MEDIASI ENTREPRENEURIAL MARKETING PADA UMKM PARIWISATA KREATIF DI BALI - Permatha Korry, Putu Dyah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.07.TAHUN.2025DO - 10.24843/EEB.2025.v14.i07.p11, 2025)
This study aims to analyze the influence of entrepreneurial capital including human, social, and symbolic capital on the collaborative capability of MSMEs, both directly and through the mediating role of entrepreneurial marketing (EM). The research was conducted among MSMEs in Bali’s creative and tourism sectors, which face market volatility, resource limitations, and sustainability pressures. Using Partial Least Square Structural Equation Modeling (PLS-SEM), the findings reveal that human and symbolic capital significantly affect collaborative capability, while social capital does not. Conversely, only social capital has a significant impact on EM, with human and symbolic capital showing no such effect. A particularly intriguing result is that EM has a negative impact on collaborative capability and negatively mediates the relationship between symbolic capital and collaboration. This indicates that personal branding driven by symbolic capital may hinder strategic partnerships. The study contributes theoretically by integrating entrepreneurial capital and dynamic capability perspectives in MSME collaboration, and offers practical insights for empowering local culture-based enterprises.